Response of milk production to price in the state of São Paulo, Brazil - Vicente, José R.; Vicente, Maria C. M. (Pesquisa Agropecuaria Brasileira, 1991)
A polynomial lag model is used to measure the influence of received price on milk production. The results showed that the monthly production is affected by the average price between third and twelfth preceding months and the annual production is influenced by the price between second and seventh preceding years. The estimated price elasticities were between 0.02 and 0.09.